2018
DOI: 10.1002/acm2.12318
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of respiratory motion tracking using Microsoft Kinect v2 sensor

Abstract: PurposeTo present and evaluate a straightforward implementation of a marker‐less, respiratory motion‐tracking process utilizing Kinect v2 camera as a gating tool during 4DCT or during radiotherapy treatments.MethodsUtilizing the depth sensor on the Kinect as well as author written C# code, respiratory motion of a subject was tracked by recording depth values obtained at user selected points on the subject, with each point representing one pixel on the depth image. As a patient breathes, specific anatomical poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
(8 reference statements)
0
22
1
Order By: Relevance
“…Depth sensors can also be used for respiratory motion tracking during radiotherapy. A good agreement was found between the Microsoft Kinect v2 and the more commonly used Anzai Respiratory Gating System and Varian's RPM system [262]. The characteristics and ease of use of depth sensors [262] provide interesting avenues for improving radiotherapy management.…”
Section: Measurement and Computingmentioning
confidence: 85%
“…Depth sensors can also be used for respiratory motion tracking during radiotherapy. A good agreement was found between the Microsoft Kinect v2 and the more commonly used Anzai Respiratory Gating System and Varian's RPM system [262]. The characteristics and ease of use of depth sensors [262] provide interesting avenues for improving radiotherapy management.…”
Section: Measurement and Computingmentioning
confidence: 85%
“…Using a Kinect v2 camera, Silverstein et al developed a system for monitoring respiration using information on the surface of the patient without markers and compared their system with existing commercial products, Varian’s Real-time Position Management (RPM) System (Varian Medical Systems, Palo Alto, CA, USA) and the Anzai belt system (Anzai Medical Co., Ltd., Tokyo, Japan). They reported that the period measurement error of their system was 77 ms to 164 ms [ 34 ]. According to the accuracy test of the RPM system used for respiratory monitoring in the present clinical cases, 99.9% of cases have an error of less than 2 mm [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Structured light plethysmography is a contactless method that may overcome the abovementioned limitations [9] but is cumbersome and unsuitable for infants inside an incubator. Due to recent advances in camera technology and computer vision, researchers have developed compact and cheap contactless solutions to monitor respiratory activity [10] [19] . Some of these solutions were designed for gating [14] , [16] and polysomnographic [11] , [17] applications and were validated in healthy adults [12] , [14] [17] or children [11] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to recent advances in camera technology and computer vision, researchers have developed compact and cheap contactless solutions to monitor respiratory activity [10] [19] . Some of these solutions were designed for gating [14] , [16] and polysomnographic [11] , [17] applications and were validated in healthy adults [12] , [14] [17] or children [11] , [13] . The infants’ small breathing movements and irregular breathing patterns limit the use of these tools in the NICU.…”
Section: Introductionmentioning
confidence: 99%